Antibody-Mediated Inhibition of CTLA4 Aggravates Atherosclerotic Plaque Inflammation and Progression in Hyperlipidemic Mice - Kikkie Poels; Mandy M. T. van Leent; Myrthe E. Reiche; Pascal J. H. Kusters; Stephan Huveneers; Menno P. J. de Winther; Willem J. M. Mulder; Esther Lutgens; Tom T. P. Seijkens (Cells, 2020)
T cell-driven inflammation plays a critical role in the initiation and progression of atherosclerosis. The co-inhibitory protein Cytotoxic T-Lymphocyte Associated protein (CTLA) 4 is an important negative regulator of T cell activation. Here, we studied the effects of the antibody-mediated inhibition of CTLA4 on experimental atherosclerosis by treating 6–8-week-old Ldlr−/− mice, fed a 0.15% cholesterol diet for six weeks, biweekly with 200 μg of CTLA4 antibodies or isotype control for six weeks. 18F-fluorodeoxyglucose Positron Emission Tomography—Computed Tomography showed no effect of the CTLA4 inhibition of activity in the aorta, spleen, and bone marrow, indicating that monocyte/macrophage-driven inflammation was unaffected. Correspondingly, flow cytometry demonstrated that the antibody-mediated inhibition of CTLA4 did not affect the monocyte populations in the spleen. αCTLA4 treatment induced an activated T cell profile, characterized by a decrease in naïve CD44−CD62L+CD4+ T cells and an increase in CD44+CD62L− CD4+ and CD8+ T cells in the blood and lymphoid organs. Furthermore, αCTLA4 treatment induced endothelial activation, characterized by increased ICAM1 expression in the aortic endothelium. In the aortic arch, which mainly contained early atherosclerotic lesions at this time point, αCTLA4 treatment induced a 2.0-fold increase in the plaque area. These plaques had a more advanced morphological phenotype and an increased T cell/macrophage ratio, whereas the smooth muscle cell and collagen content decreased. In the aortic root, a site that contained more advanced plaques, αCTLA4 treatment increased the plaque T cell content. The short-term antibody-mediated inhibition of CTLA4 thus accelerated the progression of atherosclerosis by inducing a predominantly T cell-driven inflammation, and resulted in the formation of plaques with larger necrotic cores and less collagen. This indicates that existing therapies that are based on αCTLA4 antibodies may promote CVD development in patients.